2020
DOI: 10.1055/s-0040-1710373
|View full text |Cite
|
Sign up to set email alerts
|

Barbed Sutures in Total Knee Arthroplasty: A Meta-analysis of Randomized-Controlled Trials

Abstract: Newer methods of wound closure such as barbed sutures hold the potential to reduce closure time and equivalent wound complications in various surgeries. However, few studies have compared barbed suture and conventional wound closure techniques in total knee arthroplasty (TKA). The purpose of this review was to appraise the efficacy and safety of the barbed suture in closure of TKA. We conducted a meta-analysis to identify relevant randomized-controlled trials involving barbed sutures and conventional sutures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Barbed sutures have demonstrated not only clinical advantages but also practical benefits, with faster closing times observed in both hip and knee arthroplasty procedures [25,26]. The role of skin closure is equally significant in averting wound-related complications, promoting favourable wound cosmesis, and enhancing patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbed sutures have demonstrated not only clinical advantages but also practical benefits, with faster closing times observed in both hip and knee arthroplasty procedures [25,26]. The role of skin closure is equally significant in averting wound-related complications, promoting favourable wound cosmesis, and enhancing patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Barbed sutures have demonstrated not only clinical advantages but also practical benefits, with faster closing times observed in both hip and knee arthroplasty procedures [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Barbed sutures have already been proven to result in excellent outcomes in hand surgery and surgery of the knee. A recent meta-analysis by Sun et al [ 22 ] showed that barbed sutures resulted in shorter total wound closure time ( p < 0.001) and fewer needle puncture injuries to members of the surgical team ( p = 0.02) in TKA, whereas there were no significant differences in blister formation ( p = 1.0), superficial infection ( p = 0.82), range of motion ( p = 0.94), incisional exudate ( p = 0.75), suture abscess ( p = 0.26), suture breakage ( p = 0.11), wound-related complications ( p = 0.10), or ecchymosis ( p = 0.08) between barbed and conventional wound closures [ 22 ]. However, outcomes from TKA cohorts should not be extended to outcomes expected in THA due to the anatomical and biomechanical differences in these districts.…”
Section: Discussionmentioning
confidence: 99%
“…However, of the six papers included in this study, only two included a mixed cohort of patients who underwent THA or TKA, and functional outcomes were available only for TKA patients. More recently, Sun et al [ 22 ] conducted a meta-analysis of RCTs and compared outcomes of patients who had TKA and were sutured with barbed sutures to patients who had traditional suturing, showing a lower incidence of peri-incisional ecchymosis and shorter total wound closure time. However, because of differences in anatomy, biomechanics, and the resulting forces on the soft tissue envelope between hip and knee joints, the results of studies conducted on patients with TKA may not apply to patients who had THA.…”
Section: Introductionmentioning
confidence: 99%